Detection of Cerebral Compromise With Multimodality Monitoring in Patients With Subarachnoid Hemorrhage - Chen, H Isaac; Stiefel, Michael F; Oddo, Mauro; Milby, Andrew H; Maloney-Wilensky, Eileen; Frangos, Suzanne; Levine, Joshua M; Kofke, W Andrew; LeRoux, Peter D (Neurosurgery, 2011)
Abstract BACKGROUND: Studies in traumatic brain injury suggest that monitoring techniques such as brain tissue oxygen (Pbto2) and cerebral microdialysis may complement conventional intracranial pressure (ICP) and cerebral perfusion pressure (CPP) measurements. OBJECTIVE: In this study of poor-grade (Hunt and Hess grade IV and V) subarachnoid hemorrhage (SAH) patients, we examined the prevalence of brain hypoxia and brain energy dysfunction in the presence of normal and abnormal ICP and CPP. METHODS: SAH patients who underwent multimodal neuromonitoring and cerebral microdialysis were studied. We examined the frequency of brain hypoxia and energy dysfunction in different ICP and CPP ranges and the relationship between Pbto2 and the lactate/pyruvate ratio (LPR). RESULTS: A total of 2394 samples from 19 patients were analyzed. There were 149 samples with severe brain hypoxia (Pbto2 ≤10 mm Hg) and 347 samples with brain energy dysfunction (LPR >40). The sensitivities of abnormal ICP or CPP for elevated LPR and reduced Pbto2 were poor (21.2% at best), and the LPR or Pbto2 was abnormal in many instances when ICP or CPP was normal. Severe brain hypoxia was often associated with an LPR greater than 40 (86% of samples). In contrast, mild brain hypoxia (≤20 mm Hg) and severe brain hypoxia were observed in only 53% and 36% of samples with brain energy dysfunction, respectively. CONCLUSION: Our data demonstrate that ICP and CPP monitoring may not always detect episodes of cerebral compromise in SAH patients. Our data suggest that several complementary monitors may be needed to optimize the care of poor-grade SAH patients.